ETNOGRAFI KOMUNIKASI MUSLIMAH BERCADAR DI SAMARINDA - Inayah, Sitti Syahar; Abdi, Andi Muhammad (IAIN Samarinda, 2018)
Muslim women who wear cadar (full face veil) can not explore all forms of non-verbal signs, especially facial expression, while involved in conversation since they can not show their face. However, they have developed strategy to overcome such obstacles. Muslim women who wear cadar create their own pattern of communication to allow them to have distinct rules on how to communicate among themselves. This paper, thus, aims at revealing the patterns of communication of Muslim women who wear cadar through utilizing ethnograpy of communication approach. Findings of this paper signifies that (1) women in this group wear cadar to signify that they are already enlightened in terms of religious obligations, (2) wearing cadar allows them to escape stigmas while involved in communication, and (3) unlike Indonesians in general, members of this group encourage eye contact while involved in conversations and rely on it to enlarge their chances of having meaningful conversations.Â Keywords: ethnography of communication, non-verbal language.